Playful mixture and English language learning in second-year high school students - Rosas Domínguez, Javier Dionisio (2024)
Objective. To determine if there is a relationship between playful mixtures and English language learning among high school students at Institución Educativa Mariano Dámaso Beraún in Leoncio Prado province, Huánuco region, 2019. Methods. This study is basic research at the descriptive correlational level with a non-experimental, cross-sectional design. The population consisted of 66 students. A sample of 30 students from the second grade "A" was selected using non-probabilistic sampling. For data collection, a questionnaire and a comprehension and writing test were used, validated through reliability testing and expert judgment. The hypothesis was tested using Spearman's rho coefcient. Results. The Spearman's rho coefcient test regarding the general hypothesis (relationship between playful mixtureand English learning) was 0.722 with a p-value = 0.000. Concerning the frst specifc hypothesis (relationship between playful mixture and reading various types of texts), a correlation of 0.576 and a p-value = 0.05 was obtained; for the second specifc hypothesis (relationship between playful mixture and writing various types of texts), the result was0.641 with a p-value = 0.05. All three results indicate a moderate positive correlation. Conclusions. There is a signifcant moderate correlation between the playful mixture variable and English learning among second-grade “A” students at I.E. Mariano Dámaso Beraún, 2019